Miss Pinoy - Fajardo, Bona; Bluart Production (Bluart Production, 2006)
Digital film 'Miss Pinoy' is a fiction inspired by a true story of a group of overseas Filipino Workers (OFWs) who looked for a good investment in preparation for their eventual return to the Philippines but turned out to become victims of a million dollar fraud. Together they triumphed over insurmountable odds, gained the support of the media, help of NGOs, and attention of the gov't... they were able to prove themselves, being down a deceitfully influential person to his knees, and get back what was rightfully theirs.